PECULIARITIES OF THE OPPORTUNISTIC INFECTION DIAGNOSTICS AND PHARMACOTHERAPY AMONG CHILDREN - S.V. Korzh (Педиатрическая фармакология, 2008)
The article describes the modern approaches to the opportunistic infection diagnostics and pharmacotherapy among children. the author reviews the general laws for the emergence, clinical course and diagnostics of the above mentioned infections in childhood and highlights the issues of diagnostics and pharmacotherapy of certain opportunistic infections: mycoplasmal and chlamydia infections. The article points out to the troubles, appearing in the course of diagnostics and pharmacotherapy of the given diseases among children.Key words: opportunistic infections, clamidiosis, mycoplasmosis, treatment, children.